Mejorando la experiencia de terapias ocupacionales ofrecidas para niños con parálisis cerebral. (2019)
Purpose - ​Cerebral palsy is the involvement of some parts of the brain that control the movement of the individual, this diagnosis is not progressive and has permanent damage, therefore, the treatments offered for these cases can be indefinite. The purpose of this project is to increase the motivation on the part of patients with cerebral palsy through an interactive entertainment device that will have similar functions to the activities carried out in conventional occupational therapies. Findings - ​It is necessary the union of the two most important factors found in the investigation which is the use of a physical and digital device that manages to adapt not only to the needs of the patients but also to their personal tastes, in order to guarantee interest and feeling of ownership with the device. On the other hand it is pertinent to make use of activities that are not only focused on the entertainment of patients, but on the development of their psychomotor skills. Originality/Value – ​It is a device focused on the rehabilitation of patients with cerebral palsy, which combines functionality with entertainment, making users feel comfortable with their use, and do not realize that they are carrying out activities for therapeutic purposes.